Safety and Effectiveness of Ultrasound-Guided Carpal Tunnel Release: A Systematic Review - Marcin Piwnik; Klaudia Marek; Adam Kwapisz; Elżbieta Miller (Journal of Clinical Medicine, 2026)
Background: Carpal tunnel syndrome is the most common entrapment neuropathy of the upper limb and an important cause of pain, sensory disturbance, and hand dysfunction. Open and endoscopic carpal tunnel release are effective, but they may be associated with scar-related pain, wound complications, and delayed return to work. Ultrasound-guided techniques have been developed to reduce soft-tissue trauma, enable real-time visualization of neurovascular structures, and facilitate faster recovery. Methods: A systematic search of PubMed, PubMed Central, and Scopus was conducted according to PRISMA guidelines for English-language studies published over the last 14 years. Eligible studies reported ultrasound-guided carpal tunnel release techniques and/or compared them with open, mini-open, or endoscopic procedures. Data on procedural technique, study population, follow-up, clinical outcomes, complications, and methodological characteristics were extracted and qualitatively synthesized. Results: Twenty-eight studies were included. Sample sizes ranged from 14 to 152 patients, and follow-up ranged from 3 to 74 months. The most frequently reported ultrasound-guided approaches were device-assisted carpal tunnel release, thread carpal tunnel release, and percutaneous carpal tunnel release. Most studies reported clinically meaningful improvement in symptoms and hand function, small incisions, rapid return to daily activities, and low rates of serious complications. Reported adverse events were mostly minor and transient. However, the evidence was limited by small samples, heterogeneous outcomes, single-center designs, limited long-term follow-up, and potential conflicts of interest. Conclusions: Ultrasound-guided carpal tunnel release appears to be a promising, minimally invasive alternative to traditional surgery, though current evidence is of low certainty. Larger independent comparative trials with standardized outcomes and long-term follow-up are needed.